Crisis comunications in a changing world - Seymour, Mike (2010)
This anide focuses on the characteristics of a crisis, and examines the new tendencies that have changed the way in which any management should respond and communicate whenin crisis. After defining che meaning of crisis, che three key factors of a crisis that should be included in the fores ighr plan are analyzed, namely: a) crisis should be handled openly; b)acknowledge that any insight on the evcnts will replace the actual facts; and, e) any gap in the information flow will be fi lled wirh rumors, speculations, prejudgmcnts, and accusations made by "cxperrs" or leaders of opinion. The Toyota case - experienced at rhe beginning of the USA's crisis - is ser as an example of recent ill insight. To conclude, chis article provides guidelines for communicators of crisis, and highlights the need to be ready and prepared to face any eventual crisis of companies or insri tucions.